La casa de cartón - Valdelomar Collantes, Cynthia Elizabeth (2019)
The session entitled "La Casa de Cartón” by Martin Adam, was developed taking into account the understanding of texts, the elements of the work were identified and used to show the importance of this work in 20th-century Peruvian literatura Activities were developed to analyze fragments of the aforementioned work, relating the elements of the work in question to determine its importance in 20th-century Peruvian literatura. _x000D_ The session implemented motivating activities that encouraged the achievement of its reading skills and abilities. In addition, pedagogical processes such as motivation, exploration of knowledge, problematization, management and accompaniment, evaluation of transfer into the area's teaching processes. The constant and active participation of students individually as a group was promoted. The strategies executed were in line with the interests and needs they showed